Analisis Dampak Putusan Mahkamah Konstitusi Terhadap Etika Penyelenggara Pemilu - Harid Fendra; Indah Adi Putri; Ria Ariany (Pencerah, 2022)
Law number 7 of 2017 has given a mandate to the Election Organizing Honorary Council (DKPP) as the body tasked with assessing and deciding the code of ethics for election organizers with a